EVALUATION OF MICROVESICLES FORMED BY NATURAL KILLER (NK) CELLS USING FLOW CYTOMETRY - V. A. Mikhailova; K. L. Belyakova; L. P. Vyazmina; A. R. Sheveleva; S. A. Selkov; D. I. Sokolov (Медицинская иммунология, 2018)
As a result of activation and/or apoptosis, the cells can form microvesicles (MV) from 100 nm up to 1000 nm in size. Nowadays, the attention is being increasingly focused on dynamic detection and evaluation of leukocyte-derived microvesicles by their contents. In this regard, determination of microvesicles formed by NK cells is of utmost interest. The main function of these population is to induce apoptosis of virus-infected and tumor cells. At the present time, there is no direct evidence of the NK cells ability to produce microvesicles. This investigation was performed in order to estimate contents of NK cell-derived microvesicles using highprecision flow cytometric approach. It has been shown that the high-precision flow cytometry allows to detect microvesicles formed by NK cells, ranging from 200 to 1000 nm in size. It was demonstrated that incubation of NK cells in the presence of TNFα did not affect the relative value of microvesicles, however, being associated with increased intensity of CD95 expression on microvesicles. Hence, the high-precision flow cytometry can be used to detect microvesicles and to determine their phenotype.